2017
DOI: 10.1016/j.celrep.2017.11.038
|View full text |Cite
|
Sign up to set email alerts
|

ATP Citrate Lyase Regulates Myofiber Differentiation and Increases Regeneration by Altering Histone Acetylation

Abstract: ATP citrate lyase (ACL) plays a key role in regulating mitochondrial function, as well as glucose and lipid metabolism in skeletal muscle. We report here that ACL silencing impairs myoblast and satellite cell (SC) differentiation, and it is accompanied by a decrease in fast myosin heavy chain isoforms and MYOD. Conversely, overexpression of ACL enhances MYOD levels and promotes myogenesis. Myogenesis is dependent on transcriptional but also other mechanisms. We show that ACL regulates the net amount of acetyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 26 publications
2
37
0
Order By: Relevance
“…In injured muscles, increased glycolysis may generate the glycolytic intermediates necessary for the production of new biomass and metabolites utilized by histone-and DNA-modifying enzymes whereas oxidative phosphorylation would generate the ATP required for MuSC proliferation (Ryall et al, 2015a;Pala et al, 2018). Indeed, metabolites generated by different metabolic pathways regulate the activity of chromatin-modifying enzymes known to control different aspects of MuSC biology (McKinnell et al, 2008;Juan et al, 2011;Kawabe et al, 2012;Liu et al, 2013;Ryall et al, 2015b;Boonsanay et al, 2016;Faralli et al, 2016;Scionti et al, 2017;Das et al, 2017;Tosic et al, 2018;Puri and Mercola, 2012). For instance, the oscillation of intermediary metabolites of the NAD biosynthetic pathways may be relevant for circadian gene expression in MuSCs and skeletal muscle (Nakahata et al, 2009;Ryall et al, 2015b;Solanas et al, 2017;Andrews et al, 2010;Lowe et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In injured muscles, increased glycolysis may generate the glycolytic intermediates necessary for the production of new biomass and metabolites utilized by histone-and DNA-modifying enzymes whereas oxidative phosphorylation would generate the ATP required for MuSC proliferation (Ryall et al, 2015a;Pala et al, 2018). Indeed, metabolites generated by different metabolic pathways regulate the activity of chromatin-modifying enzymes known to control different aspects of MuSC biology (McKinnell et al, 2008;Juan et al, 2011;Kawabe et al, 2012;Liu et al, 2013;Ryall et al, 2015b;Boonsanay et al, 2016;Faralli et al, 2016;Scionti et al, 2017;Das et al, 2017;Tosic et al, 2018;Puri and Mercola, 2012). For instance, the oscillation of intermediary metabolites of the NAD biosynthetic pathways may be relevant for circadian gene expression in MuSCs and skeletal muscle (Nakahata et al, 2009;Ryall et al, 2015b;Solanas et al, 2017;Andrews et al, 2010;Lowe et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As such, HDACi treatment at the onset of differentiation by serum removal abolishes differentiation. Further supporting this idea, Acly knockdown in proliferation conditions induces differentiation (Bracha et al, 2010), while knockdown in differentiation conditions reduces muscle gene expression and myotube hypertrophy (Das et al, 2017). Recent insights from single-cell ATAC-seq agree with this idea (Pliner et al, 2018), wherein differentiation begins with closing of a large number of sites, followed by a subset of specific sites that gain acetylation and accessibility (of which 70% are bound by MYOD1) (Cao et al, 2010).…”
Section: Discussionmentioning
confidence: 78%
“…We also did not observe any significant changes of IL-4-induced target gene mRNA expression upon overexpression of ACLY in MDMs (Supplementary Figure 1). Since the impact of ACLY on gene expression is linked to reduced acetylation of histone proteins in macrophages (14) and other cells (9, 13), we analyzed acetylation of lysine 27 and 14 on histone H3. Acetylation of H3K14 and H3K27 was previously shown to respond to alterations of ACLY activity (12, 26).…”
Section: Resultsmentioning
confidence: 99%
“…ACLY role in epigenetic control was initially described for cancer cells (9), where ACLY critically supports de novo lipogenesis and thus, cell proliferation (10, 11). Further studies reported epigenetic regulation through ACLY in adipocytes (9, 12) or myocytes (13).…”
Section: Introductionmentioning
confidence: 96%